The impact of mode of delivery on parent-infant-bonding and the mediating role of birth experience: a comparison of mothers and fathers within the longitudinal cohort study DREAM - Svenja Döblin; Lara Seefeld; Victoria Weise; Marie Kopp; Susanne Knappe; Eva Asselmann; Julia Martini; Susan Garthus-Niegel (BMC, 2023)
Abstract Background The association between mode of delivery (MOD) and parent-infant-bonding has only been studied in mothers and findings have been inconclusive. The aim of this study was to prospectively investigate how MOD relates to postpartum parent-infant-bonding in both mothers and fathers and whether these associations are mediated by birth experience. Methods This study is part of the prospective cohort study "Dresden Study on Parenting, Work, and Mental Health" (DREAM). Our sample comprised N = 1,780 participants who completed quantitative questionnaires during pregnancy as well as 8 weeks and 14 months postpartum. MOD was dummy coded, contrasting spontaneous vaginal delivery against vaginal delivery induced by drugs, operative vaginal delivery, planned, and unplanned cesarean section. Parent-infant bonding and birth experience were assessed using validated scales. A moderated mediation analysis based on ordinary least square (OLS) regression and bootstrapped estimates was conducted, considering relevant confounding variables. Results Compared to spontaneous vaginal delivery, all categories of MOD predicted more negative birth experiences in both parents. A more positive birth experience predicted stronger parent-infant-bonding at 8 weeks, but not at 14 months postpartum. Mothers who delivered via cesarean section (planned or unplanned) reported stronger parent-infant-bonding at 8 weeks and 14 months postpartum. In fathers, only unplanned cesarean section was associated with stronger parent-infant-bonding at 8 weeks postpartum. At 8 weeks postpartum, birth experience mediated the association between a vaginal delivery induced by drugs and a planned cesarean section and mother-infant-bonding and between a vaginal delivery induced by drugs, an operative vaginal delivery, and planned cesarean section and father-infant-bonding. At 14 months postpartum, birth experience mediated the association between a vaginal delivery induced by drugs, operative vaginal delivery, and planned cesarean section and parent-infant-bonding in both parents. Conclusions The results emphasize the importance of the birth experience for parent-infant-bonding in both mothers and fathers. Further research should address the mechanisms by which parents with an unplanned cesarean section establish stronger parent-infant-bonding compared to parents whose baby was delivered via spontaneous vaginal delivery, despite their overall more negative birth experiences.